2019
DOI: 10.1093/eurheartj/ehz395
|View full text |Cite
|
Sign up to set email alerts
|

Digoxin–mortality: randomized vs. observational comparison in the DIG trial

Abstract: Aims The Digitalis Investigation Group (DIG) trial, the only large randomized trial of digoxin in heart failure, reported a neutral effect on mortality and a significant reduction in heart failure hospitalizations. Recent observational studies reported increased mortality with digoxin treatment. We present further analyses of the DIG trial displaying the inability to control bias in observational treatment comparisons despite extensive statistical adjustments. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(34 citation statements)
references
References 25 publications
1
31
1
1
Order By: Relevance
“…We have made efforts to adjust for differences in baseline characteristics between patients with AF and sinus rhythm and across heart rate tertiles. Despite this, as is inherent in any analysis of this nature, the risk of residual confounding remains high and our findings should be interpreted in context of this . Our results do not extend to those patients who were not eligible for inclusion in the clinical trials, for example, those with HFpEF or severe renal impairment.…”
Section: Strengths and Limitationscontrasting
confidence: 56%
“…We have made efforts to adjust for differences in baseline characteristics between patients with AF and sinus rhythm and across heart rate tertiles. Despite this, as is inherent in any analysis of this nature, the risk of residual confounding remains high and our findings should be interpreted in context of this . Our results do not extend to those patients who were not eligible for inclusion in the clinical trials, for example, those with HFpEF or severe renal impairment.…”
Section: Strengths and Limitationscontrasting
confidence: 56%
“…Nonrandom assignment to digoxin treatment in study participants is reflected in differences between groups in Table 2. There are reports suggesting that prescription bias in observational digoxin studies far exceeds the true effect of the treatment, and thus, even after adjustment, they fail to capture the real consequences of the medication 29. Since digoxin would have been added as 3rd line agent in patients without HF, it can be assumed that rate control was difficult and these patients would have had higher mortality regardless of digoxin use in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…The particular strengths of the current analysis is (i) the derivation of the data from two very large randomized trials in HFrEF with meticulously adjudicated clinical endpoints, (ii) the adjustment for many prospectively assessed clinical and laboratory variables including NT‐proBNP as well as drug treatment, and (iii) the derivation of rhythm and heart rate from baseline electrocardiograms (ECGs) in all patients, thus avoiding potential underestimation of ventricular heart rate by pulse taking in patients with AF. Nevertheless, as in all retrospective analyses, despite widespread correction for potential bias, unknown confounders cannot be completely excluded …”
Section: Fundingmentioning
confidence: 99%
“…In the meantime, digitalis glycosides may be used in selected patients, provided that the levels of the drugs are controlled regularly (target digoxin: 0.5–0.9 ng/mL; digitoxin: 8–18 ng/mL), especially in the case of digoxin that is cleared predominantly by the kidney . While in retrospective non‐randomized analyses digoxin was supposed to be associated with worse outcomes, further analyses have shown that these assumptions result mainly from prescription bias and not from an adverse drug effect . Recently in older patients hospitalized for heart failure, discontinuation of pre‐admission digoxin therapy was even associated with poor outcomes, albeit this study was not randomized .…”
Section: Fundingmentioning
confidence: 99%